Design and Life Cycle Cost Analysis of a Forward Converter Feded Solar Powered 3-phase Water Motor - Hossain, Mohammad Shahadat; Chowdhury, Imtiaz Akber; Chakma, Rocky; Hoque, Ashraful (Trends in Sciences, 2022)
Supply of water for irrigation and household use is not adequate in rural Bangladesh during dry season. To ensure continuous water supply for irrigation and other household activities in rural Bangladesh, where the supply of uninterrupted electricity is hardly available all the time and mostly irrigation is done by Diesel-based water pump. The paper proposes a standalone model to run a 3-phase motor in such condition. Due to the continuous reduction of price of electrical and electronic components related to solar panel, solar based pumping system has become the most economically viable option to mitigate this problem related to larger rural community. Output from the solar cell is converted to stable high DC voltage by incorporating a single stage forward converter. Switching circuit for 3-phase inverters is simulated in Power Sim (PSIM) which maintains the smooth operation of the water motor. The T-LCL filter is introduced to reduce the voltage ripple to a tolerance level before being fed to the motor. Forward converter based proposed system has a better total harmonic distortion (THD) of 0.087 with different output voltage as required. The conventional Diesel-based system not only pollutes the environment but also the total of capital investment and maintenance cost is more than 3 times higher than the proposed Forward converter and 3-phase sinusoidal pulse-width modulation (SPWM) inverter-based system. This model can be a good solution considering the unavailability, high price and environmental issues of fuel-based power supply. HIGHLIGHTS Due to the lack of uninterrupted electricity facility in the rural area of Bangladesh, a Diesel-based water pump is used which is quite expensive and not environment friendly To mitigate the aforementioned problem, nowadays solar-based pumping system attracts significant attention The Proposed Forward converter and 3-phase sinusoidal pulse-width modulation (SPWM) inverter-based system can be an optimum solution regarding price, environment, and continuous supply issues GRAPHICAL ABSTRACT